Continuous Nanoparticle Patterning Strategy in Layer‐Structured Nanocomposite Fibers. (25th June 2022) - Xu, Weiheng; Franklin, Rahul; Ravichandran, Dharneedar; Bawareth, Mohammed; Jambhulkar, Sayli; Zhu, Yuxiang; Kakarla, Mounika; Ejaz, Faizan; Kwon, Beomjin; Hassan, Mohammad K.; Al‐Ejji, Maryam; Asadi, Amir; et al.
Abstract: Anisotropic polymer/nanoparticle composites display unique mechanical, thermal, electrical, and optical properties depending on confirmation and configuration control of the composing elements. Processes, such as vapor deposition, ice‐templating, nanoparticle self‐assembly, additive manufacturing, or layer‐by‐layer casting, are explored to design and control nanoparticle microstructures with desired anisotropy or isotropy. However, limited attempts are made toward nanoparticle patterning during continuous fiber spinning due to the thin‐diameter cross section and 1D features. Thus, this research focuses on a new patterning technique to form ordered nanoparticle assembly in layered composite fibers. As a result, distinct layers can be retained with innovative tool design, unique material combinations, and precise rheology control during fiber spinning. The layer multiplying‐enabled nanoparticle patterning is demonstrated in a few material systems, including polyvinyl alcohol (PVA)–boron nitride (BN)/PVA, polyacrylonitrile (PAN)–aluminum (Al)/PAN, and PVA–BN/graphene nanoplatelet (GNP)/PVA systems. This approach demonstrates an unprecedentedly reported fiber manufacturing platform for well‐managed layer dimensions and nanoparticle manipulations with directional thermal and electrical properties that can be utilized in broad applications, including structural supports, heat exchangers, electrical conductors, sensors, actuators, and soft robotics. Abstract : Alternating layers of boron nitride (BN) nanoparticles and polyvinyl alcohol (PVA) are continuously fabricated via fluidic property‐driven fiber spinning technique where the pattern resolution is not limited by nozzle feature size. Vertically aligned BN channels, with a minimum thickness of 2 µm, show high thermal conductivity compared to homogeneously mixed BN/PVA fiber.